Linear Non-Threshold (LNT) historical discovery milestones - Calabrese, Edward (La Medicina del Lavoro, 2022)
The present paper provides a summarized identification of critical historical milestones in the discovery of the flawed and corrupt foundations of cancer risk assessment, with particular focus on the LNT Dose Response model. The milestone sequence presented herein is based on a large body of published findings by the author. The history of LNT and cancer response represents what may be the most significant case of scientific misconduct reported in the US, with its revelation severely damaging the scientific credibility and moral authority of leading US regulatory agencies and organizations such as the National Academy of Sciences (NAS) and the journal Science. The consequences of this corrupt history are substantial, affecting cancer risk assessment throughout the world, critical aspects of national economies, the development of critical technologies and public health practices.